Tolerância do arroz de terras altas (Oryza sativa L.) ao declínio da produção de grãos causado por seu monocultivo - Costa, Sílvia Sobral (1997)
Upland rice presents great yield reductions when cultivated as a monocrop. This phenomenon is considered by traditional rice growers as a result of tired soils. The reasons for reduced grain production, however, may be of several causes (low soil fertility, diseases, pests, decline in organic matter content, etc.) but the most important of them emphasized in the related literature refers to the allelopatic reaction by the rice crop, mainly to the autotoxicity. The lack of knowledge about this subject in Brazil, has been the source of systematic economic damage. On one hand by continuous crop establishment in the same area for several years and, on the other, by returning the rice crop to the old area before allowing sufficient time to the soil to recuperate. Additionally, it is common, especially in the northern states, the traditional crop system of slash burn, on a migratory way to avoid soil sickness. This is a non sustainable and poluent way to explore the field. The objective of this study was to evaluate a representative germplasm of the japonica tropical rice for its tolerance to monocrop system and analyze the possibility to reduce the problem by breeding procedure. The tests were established in the three areas with different antecedents. System 1 - rice after four years of maize; System 2 – two years of rice after three years of maize; System 3 – Four years of rice (monocrop) after one year of maize. The 95 genotypes tested were divided into three groups: Group 1- 17 commercial varieties; Group 2 – 17 traditional varieties; Group 3 – 61 advanced lines. Highly significant differences were observed among the systems, with a decline in production of 43% due to monocrop on its most severe condition (system 3). The commercial varieties yielded as much as the advanced lines, but 47,34% and 32,88% more than traditional ones, respectively on systems 1 and 3. The monocrop system increased plant cycle up to one week, on the average, and reduced plant height in 11 cm. The observed differences among and within genotype groups, as well as its interactions with the crop systems show the existence of genetic variability and the genotypes do not react to monocrop on the same way. With the average heritability among groups of 0,67 and with a selection intensity of 30% it was possible to estimate an average gain of 24,4% on the system 3. These genetic parameters show the possibility to attain a better agronomic behavior of rice in monocrop through breeding approach.